Cell free Microcystis aeruginosa spent medium affects Daphnia magna survival and stress response. (May 2021) - Bojadzija Savic, Gorenka; Colinet, Hervé; Bormans, Myriam; Edwards, Christine; Lawton, Linda A.; Briand, Enora; Wiegand, Claudia
Abstract: Primary consumers in freshwater ecosystems, such as the zooplankton organism Daphnia magna, are highly affected by cyanobacteria, both as they may use it as a food source but also by cyanobacterial metabolites present in the water. Here, we investigate the impacts of cyanobacterial metabolites focussing on the environmental realistic scenario of the naturally released mixture without crushing cyanobacterial cells or their uptake as food. Therefore, D. magna were exposed to two concentrations of cell free cyanobacterial spent medium from Microcystis aeruginosa PCC 7806 to represent higher and lower ecologically-relevant concentrations of cyanobacterial metabolites. Including microcystin-LR, 11 metabolites have been detected of which 5 were quantified. Hypothesising concentration and time dependent negative impact, survival, gene expression marking digestion and metabolism, oxidative stress response, cell cycle and molting as well as activities of detoxification and antioxidant enzymes were followed for 7 days. D. magna suffered from oxidative stress as both catalase and glutathione S-transferase enzyme activities significantly decreased, suggesting enzyme exhaustibility after 3 and 7 days. Moreover, gene-expressions of the 4 stress markers (glutathione S-transferase, glutathione peroxidase, catalase and thioredoxin) were merely downregulated after 7 days of exposure. Energy allocation (expression of glyceraldehyde-3-phosphate dehydrogenase) was increased after 3 days but decreased as well after 7 days exposure. Cell cycle was impacted time dependently but differently by the two concentrations, along with an increasing downregulation of myosin heavy chain responsible for cell arrangement and muscular movements. Deregulation of nuclear hormone receptor genes indicate that D. magna hormonal steering including molting seemed impaired despite no detection of microviridin J in the extracts. As a consequence of all those responses and presumably of more than investigated molecular and physiological changes, D. magna survival was impaired over time, in a concentration dependent manner. Our results confirm that besides microcystin-LR, other secondary metabolites contribute to negative impact on D. magna survival and stress response. Highlights: Cell free M. aeruginosa spent medium had negative effect on Daphnia survival and stress response. Spent medium with higher concentration of cyanobacterial metabolites was more detrimental. Other secondary metabolites, besides microcystin-LR highly likely had negative impact on Daphnia .